Split cornea transplantation for 2 recipients - review of the first 100 consecutive patients - Heindl, Ludwig M.; Riss, Stephan; Laaser, Kathrin; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (American Journal of Ophthalmology, 2011)
To evaluate the feasibility of split cornea transplantation for 2 recipients by combining deep anterior lamellar keratoplasty (DALK) and Descemet membrane endothelial keratoplasty (DMEK).Interventional case series.Fifty consecutive eyes with anterior stromal disease suitable for DALK and 50 eyes with endothelial disease suitable for DMEK were scheduled for split cornea transplantation combining both procedures within 72 hours. Main outcome measures included success of using a single donor cornea for 2 recipients, best spectacle-corrected visual acuity (BSCVA), and complication rates within 6 months' follow-up.A single donor cornea could be used for 2 recipients in 47 cases (94%). In 3 eyes (6%), the DALK procedure had to be converted to penetrating keratoplasty (PK) requiring a full-thickness corneal graft. Thereby, 47 donor corneas (47%) could be saved. Six months after surgery, mean BSCVA was 20/36 in the 47 eyes that underwent successful DALK, 20/50 in the 3 eyes that underwent conversion from DALK to PK, and 20/29 in the 50 eyes that underwent DMEK. Postoperative complications after DALK included Descemet folds in 5 eyes (11%) and epitheliopathy in 3 eyes (6%). After DMEK, partial graft detachment occurred in 26 eyes (52%) and was managed successfully with intracameral air reinjection. All corneas remained clear up to 6 months after surgery. No intraocular infections occurred.Split use of donor corneal tissue for combined DALK and DMEK procedures in 2 recipients within 3 subsequent days is a feasible approach to reduce donor shortage in corneal transplantation in the future.
EVALuna2:21041